2024
DOI: 10.1002/smtd.202301338
|View full text |Cite
|
Sign up to set email alerts
|

Droplet‐Based Glycan and RNA Sequencing for Profiling the Distinct Cellular Glyco‐States in Single Cells

Sunanda Keisham,
Sayoko Saito,
Satori Kowashi
et al.

Abstract: Plate‐based single‐cell glycan and RNA sequencing (scGR‐seq) is previously developed to realize the integrated analysis of glycome and transcriptome in single cells. However, the sample size is limited to only a few hundred cells. Here, a droplet‐based scGR‐seq is developed to address this issue by adopting a 10x Chromium platform to simultaneously profile ten thousand cells' glycome and transcriptome in single cells. To establish droplet‐based scGR‐seq, a comparative analysis of two distinct cell lines is per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…1 Recent research using blotting electrophoresis of RNA extracted from cells showed that small RNAs on the living cell surface were Nglycosylated and terminated with sialic acids (Sias). 7 Mass spectrometry, 8 high-performance anion-exchange chromatography, 9 and RNA sequencing 10 were also applied to the in vitro detection of glycoRNA. However, these in vitro analysis techniques discarded the location information on the sialylated RNA and could not provide the number of the glycosylation sites or the potential functions of the glycosylated RNAs (glycoRNAs).…”
Section: ■ Introductionmentioning
confidence: 99%
“…1 Recent research using blotting electrophoresis of RNA extracted from cells showed that small RNAs on the living cell surface were Nglycosylated and terminated with sialic acids (Sias). 7 Mass spectrometry, 8 high-performance anion-exchange chromatography, 9 and RNA sequencing 10 were also applied to the in vitro detection of glycoRNA. However, these in vitro analysis techniques discarded the location information on the sialylated RNA and could not provide the number of the glycosylation sites or the potential functions of the glycosylated RNAs (glycoRNAs).…”
Section: ■ Introductionmentioning
confidence: 99%